Nystagmus and Related Fixation Instabilities Following Extraction of Unilateral Infantile Cataract in the Infant Aphakia Treatment Study (IATS) - Felius, Joost (Invest Ophthalmol Vis Sci, 2014)
PURPOSE. To study eye movements in a large group of children after the removal of unilateral infantile cataract, and to compare fixation instabilities between treatment groups with or without IOL implantation. METHODS. The Infant Aphakia Treatment Study (IATS) is a randomized, multicenter clinical trial comparing IOL to contact lens (CL) treatment with a unilateral infantile cataract in participants who underwent cataract surgery at 1 to 6 months of age. At age 4.5 years, eye movements were recorded in 103 participants, using a high-speed video camera while the child performed a fixation task. The recordings were inspected by masked readers for the presence of fixation instabilities (nystagmus and saccadic oscillations). RESULTS. Overall, fixation instabilities were observed in 50 (60%) of 83 children who had evaluable recordings, with no differences between treatment groups (27 [64%] of 42 in the IOL group, 23 [56%] of 41 in the CL group; P = 0.51). Nystagmus was seen in 38% and saccadic oscillations in 31%, with no differences between treatment groups (P > 0.33). Children without a fixation instability had better visual acuity (P = 0.04). CONCLUSIONS. Nystagmus and saccadic oscillations are well-known consequences of infantile cataracts, presumably the result of visual deprivation during the critical period of visual development. After early cataract extraction, successful optical correction may reduce further form deprivation and minimize the incidence of these fixation instabilities. In this study, no differences in the presence of fixation instabilities were found between the two treatment strategies (CL or IOL) for optical correction after cataract removal. (ClinicalTrials.gov number, NCT00212134.)